Interactive Multimedia Learning Objects: A Pathway to Boost Reading Interest of Mentally Impaired Students - Mardiana, Mardiana; Munir, Munir; Wahid, Abdul (Indonesian Journal of Educational Studies, 2025)
This study aims to explore the impact of Interactive Multimedia Learning Objects (IMLO) on the reading interest of mentally impaired students at SLB Al Qasmi Watampone. Using a qualitative descriptive approach, data were collected through classroom observation, teacher interviews, and document analysis. The focus was on four key indicators of reading interest: joyful feeling, willingness, attention, and participation, as adapted from Slameto (2010). Five students with mentally impaired were observed during reading sessions that incorporated IMLO, while two teachers provided insights on students' behavior and learning progress. The findings revealed that the use of IMLO significantly improved students’ engagement in all four aspects of reading interest. Students showed greater emotional enjoyment, motivation, focus, and active involvement in reading activities when interacting with multimedia-based materials. Teachers noted that IMLO encouraged autonomy and curiosity, although limitations such as limited device access, the need for supervision, and weak memory retention remained challenges. Overall, IMLO proved to be an effective tool for supporting literacy development among mentally impaired students. The study suggests that with adequate infrastructure and teacher training, IMLO can be implemented successfully in inclusive education settings to enhance student motivation and participation in reading.